The psychological impact of COVID-19 and other viral epidemics on frontline healthcare workers and ways to address it: A rapid systematic review (2020)
Background As the world is battling the COVID-19 pandemic, frontline health care workers (HCWs) are among the most vulnerable groups at risk of mental health problems. The many risks to the wellbeing of HCWs are not well understood. Of the literature, there is a paucity of information around how to best prevent psychological distress, and what steps are needed to mitigate harm to HCWs’ wellbeing. Methods A systematic review using PRISMA methodology was used to investigate the psychological impact on HCWs facing epidemics or pandemics, using three electronic databases (PubMed, MEDLINE and CINAHL), dating back to 2002 until the 21st of August 2020. The search strategy included terms for HCWs (e.g., nurse and doctor), mental health (e.g., wellbeing and psychological), and viral outbreaks (e.g., epidemic and pandemic). Only studies with greater than 100 frontline HCWs (i.e. doctors or nurses in close proximity to infected patients) were included. Results A total of 55 studies were included, with 53 using quantitative methodology and 2 were qualitative. 50 of the quantitative studies used validated measurement tools while 5 used novel questionnaires. The studies were conducted across various countries and included people with SARS (13 studies), Ebola (1), MERS (3) and COVID-19 (38). Findings suggest that the psychological implications to HCWs are variable with several studies demonstrating an increased risk of acquiring trauma or stress-related disorders, depression and anxiety. Fear of the unknown or becoming infected were at the forefront of the mental challenges faced. Being a nurse and being female appeared to confer greater risk. The perceived stigma from family members and society heightened negative implications; predominantly stress and isolation. Coping strategies varied amongst the contrasting sociocultural settings and appeared to differ amongst doctors, nurses and other HCWs. Implemented changes, and suggestions for prevention in the future consistently highlighted the need for greater psychosocial support and clearer dissemination of disease-related information. Conclusion This review can inform current and future research priorities in the maintenance of wellbeing amongst frontline HCWs. Change needs to start at the level of policy-makers to offer an enhanced variety of supports to HCWs who play a critical role during largescale disease outbreaks. Psychological implications are largely negative and require greater attention to be mitigated, potentially through the involvement of psychologists, raised awareness and better education. The current knowledge of therapeutic interventions suggests they could be beneficial but more long-term follow-up is needed.